THE EFFECT OF EXPLANT SOURCES AND GROWTH REGULATORS ON CALLUS INDUCTION AND REGENERATION IN DIFFERENT TOMATO CULTIVARS. - Najam-us-Sahar Durrani; D. Ahmad; A. Jalal; H. Rajab andM. S. Khan (Journal of Animal and Plant Sciences, 2017)
Three cultivars of tomato (Solanum lycopersicum L.)i.e. Rio Grande, Moneymaker and Gala were evaluated for their tissue culture responses on different types of media containing different formulations of growth regulators. Among the three cultivar tested on eight different callus induction media (CIM) formulations, Rio Grande was the most responsive cultivar showing 93.3% callus induction responses on CIM1, having 1 mgL-1 BAP and 0.1 mgL-1 NAA, followed by Moneymaker with 46.67% callus induction responseson CIM7 containing 0.5 mgL-1 BAP, 0.5 mgL-1 NAA, 0.5 mgL-1 IAA and 1 mgL-1 Kinetin fromhypocotyl explants.Among the eight different media compositions, CIM1 resulted in maximum callus induction showing 34.1% and 27.23% average callus induction from hypocotyls and cotyledons' explants, respectively. Successfully proliferated callus were transferred to 7 types of shoot induction media (SIM). Shoot induction was observed on both SIM1 having 1 mgL-1 BAP and 0.1mgL-1 NAA and SIM2 having 2 mgL-1 BAP and 0.2 mgL-1 NAA but SIM1 showed maximum number of shoots primordia from calli. Calli with shoot primordia were transferred to shoot multiplication media i.e. MS media containing 2 mgL-1 IAA, 0.2 mgL-1 BAP, all the calli showed shoot multiplication. Rootinduction media i.e. MS or ½ MS media containing 2 mgL-1 IBA were used to induce rooting in the regenerated plantlets.Rio Grande and Moneymaker produced roots successfully and were successfully acclimatized to greenhouse after well developed rooting system.
Keywords: Solanum lycopersicum L.; callus induction; regeneration; growth regulators; Auxin; Cytokinins